Enhancing ESP Reading Comprehension through Context Clues and Digital Strategies - Himaya Praptani Adys; Himala Praptami Adys; Misnawaty Usman (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
This study investigates how economics students use context clues and digital strategies to enhance vocabulary acquisition and reading comprehension in English for Specific Purposes (ESP). The research aims to identify students’ inference patterns, compare success rates across different types of clues, and analyse the relationship between contextual inference skills and overall comprehension. Using a quantitative descriptive design, data were collected from 85 randomly selected undergraduate economics students who completed ESP reading and vocabulary tasks through both printed and digital formats. Results indicate that students achieved the highest success with definition clues (72.4%) and contrast clues (68.9%), while example clues were the most challenging (47.2%). Pearson correlation analysis revealed a strong positive relationship between the utilisation of context clues and reading comprehension (r = 0.78, p < 0.01). Regression analysis further confirmed that definition and contrast clues were the strongest predictors of comprehension performance. Findings suggest that combining explicit instruction in context clue recognition with digital scaffolding—such as pop-up glossaries and annotation tools—can significantly improve ESP reading outcomes. These strategies help learners engage actively with specialised economic texts, enhance inferencing accuracy, and foster independent vocabulary learning. The study concludes that integrating digital literacy with traditional reading strategies is essential for developing effective ESP pedagogy in the digital era, supporting both linguistic and professional competencies of economics students.